Thyroid Carcinoma After Radiotherapy of the Neck - Laviña Risso, Raúl; Perrone Noceti, Luis; González Moreno, Yamandú; Leborgne, Félix; Lorenzo, Julio; Toledo, Nancy (Cirugía del Uruguay, 1981)
A case of carcinoma of a previously irradiated thyroid gland during the treatment of a dorsal neuroblastoma is reported.